2015
DOI: 10.1021/acsami.5b01776
|View full text |Cite
|
Sign up to set email alerts
|

Lead-Free α-La2WO6 Ferroelectric Thin Films

Abstract: (001)-Epitaxial La2WO6 (LWO) thin films are grown by pulsed laser deposition on (001)-oriented SrTiO3 (STO) substrates. The α-phase (high-temperature phase in bulk) is successfully stabilized with an orthorhombic structure (a = 16.585(1) Å, b = 5.717(2) Å, c = 8.865(5) Å). X-ray-diffraction pole-figure measurements suggest that crystallographic relationships between the film and substrate are [100]LWO ∥ [110]STO, [010]LWO ∥ [11̅0]STO and [001]LWO ∥ [001]STO. From optical properties, investigated by spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 32 publications
5
23
1
Order By: Relevance
“…By comparison with ICDD-PDF cards, we identified a preferential growth direction of the film (six harmonic diffraction peak series) with a parameter of around 8.68 Å, i.e., either the c⃗ direction of the hightemperature NdWO-tetragonal variety or the c⃗ direction of the high-temperature polymorph α-LaWO, orthorhombic. 26 Indeed, the two high-temperature varieties (NdWO-tetragonal and LaWO orthorhombic) are strongly related, and only the a parameter differs between them: a LWO-ortho ∼ 3 × a NdWO-tetra , b LWO-ortho ∼ b NWO-tetra , and c LWO-ortho ∼ c NWO-tetra . However, at this step, and considering only the 00l peaks, it is not possible to discriminate them.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparison with ICDD-PDF cards, we identified a preferential growth direction of the film (six harmonic diffraction peak series) with a parameter of around 8.68 Å, i.e., either the c⃗ direction of the hightemperature NdWO-tetragonal variety or the c⃗ direction of the high-temperature polymorph α-LaWO, orthorhombic. 26 Indeed, the two high-temperature varieties (NdWO-tetragonal and LaWO orthorhombic) are strongly related, and only the a parameter differs between them: a LWO-ortho ∼ 3 × a NdWO-tetra , b LWO-ortho ∼ b NWO-tetra , and c LWO-ortho ∼ c NWO-tetra . However, at this step, and considering only the 00l peaks, it is not possible to discriminate them.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, piezoelectricity and ferroelectricity within this compound were observed by our group when stabilized in the thin-film form on SrTiO 3 and LaAlO 3 substrates. 26,27 On the one hand, Ln 2 WO 6 compounds with large cations (Ln = Ce to Dy) usually crystallize in a monoclinic fluorine-…”
Section: ■ Introductionmentioning
confidence: 99%
“…The values of E c,shift were not influenced significantly by the application of Ni nanodots. The strong shift indicates the existence of the internal built‐in electric field with stabilized polarizations in a certain direction . The significant imprint behavior has certain advantages, for example, substantially less aging in the piezoelectric response and more robustness against depolarization caused by voltage or temperature excursions …”
Section: Resultsmentioning
confidence: 99%
“…The growth of the Nb-PZT films seems to be limited by the existence of embossed electrode configuration by revealing boundaries of growing grains along with the vertical line given by the embossed area. [29][30][31] The significant imprint behavior has certain advantages, for example, substantially less aging in the piezoelectric response and more robustness against depolarization caused by voltage or temperature excursions. This film structure on the embossed electrode results in a larger effective area of the films compared to the flat structure, which is likely to be one of the reasons for the different electrical behavior.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…low-temperature -La 2 WO 6 (space group P2 1 2 1 2 1 ) (Chambrier et al, 2009a) and high-temperature -La 2 WO 6 (space group Pm2 1 n) (Allix et al, 2011). The observation of the piezoelectric effect in thin films of La 2 WO 6 (Carlier et al, 2015(Carlier et al, , 2016 confirmed the possibility of the existence of these noncentrosymmetric space groups.…”
Section: Introductionmentioning
confidence: 89%